THE IMPLEMENTATION USING VOCABULARY TO READING SKILLS AT THE ELEVENTH GRADE STUDENTS’ OF SMK AL-FARABI CILEUNGSI-BOGOR - Jumyati; Herman (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2012)
This research was taken at SMK AL-Farabi Cileungsi Bogor used classroom action research and the instrument for collecting data used observation and written test. For the written test, the writers give before implement the research and after research.. From the result of analyzing the data, obtain that the teaching using vocabulary has better for students to reading skills. The percentage result from pre-test obtain “less” (21.95%), “enough” (65.85%), and “good” (12.20%). And percentage result for post-test is “less” (0%), “enough” (9.76%), “good” (63.41%), and “excellent” (26.83%). This research explains that students at eleventh grade of SMK AL-Farabi Cileungsi Bogor, has comprehend vocabulary in the word meaning and sentence in the reading. There for, the writer hopes to teachers can introduce vocabulary deeper especially in the sentence on reading. The writers hope the students are more active in learning English Language.